The Influencing Factors of Knowledge Hiding Among Employees in the Construction Industry: A Psychological Contract Perspective - Wei Lai; Shengxiang, She; Chugong, Zhang (Apollo: Journal of Tourism and Business, 2024)
This study explores the factors influencing employee knowledge hiding in construction industry organizations. Utilizing quantitative methods, the research examines the impact of demographic factors, including gender, age, educational level, marital status, and duration of service, as well as psychological contract breaches on employee knowledge hiding. An independent samples t-test and multiple comparisons using the least significant difference (LSD) test were conducted to analyze the demographic factors. At the same time, a simple linear regression analysis was employed to assess the relationship between psychological contract breach and knowledge hiding. The results indicate that demographic factors significantly affect employee knowledge hiding, with females, older employees, those with lower educational levels, divorced or widowed individuals, and employees with longer service durations tending to hide knowledge more frequently. Furthermore, psychological contract breach is found to have a strong and positive relationship with employee knowledge hiding, suggesting that employees are more likely to engage in knowledge-hiding behaviors when they perceive a violation of their psychological contract. The findings have important managerial implications, emphasizing the need for tailored strategies to address knowledge hiding among different employee groups and maintaining a strong psychological contract with employees to foster a culture of knowledge sharing and innovation